Preidentification of high-risk pregnancies to improve triaging at the time of admission and management of complications in labour room: a quality improvement initiative. (17th June 2022) - Kumari, Prabha; Singh, Mahtab; Sinha, Shailja; Ranjan, Rajeev; Arora, Prachi; Rani, Sunita; Aggarwal, Aparna; Aggarwal, Kanika; Gupta, Shefali
Abstract : Complications can occur anytime during pregnancy and childbirth. Pregnancies associated with high-risk factors have a higher-than-normal risk for fetomaternal complications. Bhagwan Mahavir hospital is a public sector hospital catering to low-risk and high-risk pregnant women (PW) in the labour room (LR)). The obstetrics and gynaecology team observed that at times the LR team failed to identify high-risk pregnancy (HRP) during admission in LR and to manage complications timely and efficiently. Therefore, the team started a quality improvement (QI) project in January 2019 with the aim to admit preidentified HRP in LR from existing 0% to 80% in 3 months. The QI team followed the point-of-care quality improvement methodology to conduct this improvement process. They identified HRP in the outpatient department (OPD) during their antenatal care (ANC) visits, mentioned an HRP number on their ANC cards, and did risk stratification with yellow and red stickers into moderate and severe HRP respectively. Preidentified HRP were attended, admitted and managed on priority in the LR. The team achieved its aim in the ninth week of the QI initiative and sustaining to date. The team also measured and analysed the type of HRP identified in OPD, complications occurring around the process of childbirth in LR, maternal near-miss, maternal death and PW referred out from LR. They observed a 6.5%-point reduction (68.93%) in the median complication rate of major life-threatening complications following this improvement process. This new intervention facilitated the team in early initiation of management of HRP in OPD, their triaging in LR, preparedness towards managing complications, involvement of support staff, PW and their relatives in the patient care, and redistribution of human resources according to priority area. The lessons learnt are generalisable and can be used in other facilities with similar settings.